THE INFLUENCE OF COMPETENCY, MOTIVATION WORK AND DISCIPLINE WORK TO PERFORMANCE OFFICER AT THE OFFICE OF COMMUNICATIONS FULL RIVER CITY - Poni Yanita (J-MAS (Jurnal Manajemen dan Sains), 2017)
This research Aims To Reveal: (1) Effect of Competence partially to Employee Performance at the Office of Communications Full River City (2) Effect of Work Motivation partially to Employee Performance at the Office of Communications Full River City (3) Effect of Work Discipline partially to Employee Performance at the Office of Communications Full River City (4) Effect of Competence, Work Motivation and Discipline Work simultaneously To Performance Officer at the Office of Communications Full River City. The study population was all the staff of Office of Communications River City Full totaling 34 people. Samples were taken from all of the population is 34 people. Methods of analysis using simple regression analysis and multiple regression analysis. Results obtained (1) Partially Competence , Work Motivation and Work Discipline, positive and significant impact on employee performance of Communications River City Full (2) Simultaneously Influence of Competence (X1), work motivation (X2), Work Discipline (X3) on employee performance (Y) is 0.003 with Sig. F 0.003 <0.05 and Fhitung value of 5.847, while the value of F table is 2,92 so that the value of F larger than F table, it can be said that the competence (X1) work motivation (X2) and the Discipline of the work (X3) proved positive and significant influence on employee performance of Office of Communications City Full River and regression equations for these three variables is Y = 52,271+ 0,190 X1 + 0,204 X2 + 0,412 X3. Finally the authors suggest the results of this study to increase competence, work motivation and work discipline in accordance with their respective indicators and for other researchers can continue this research in order that the limitations in this study could be refined.Keywords: Competence, Work Motivation and Work Discipline and Employee Performance